MENDEL 2002 : 8th International Conference on Soft Computing. June 5-7, 2002, Brno, Czech Republic (University of Technology, 2002)
Evolutionary Computation, Genetic Programming, Fuzzy Logic, Rough Sets, Neural Networks, Fractals, Bayesian Methods